Interdisciplinary Collaboration in Improving the Quality of Primary School Education - Putri Rahmi (JKA, 2025)
Interdisciplinary collaboration in primary schools is increasingly recognized as an effective approach to improving the quality of education. This article examines the role of interdisciplinary collaboration in creating more comprehensive and engaging learning experiences for students. This research uses qualitative methods with case study analysis from several schools that have implemented interdisciplinary collaboration. The results show that implementing this collaboration not only improves students' conceptual understanding but also increases their learning engagement and motivation. However, challenges such as lack of teacher training and structural support are obstacles to implementation. This article recommends the importance of policy support and ongoing training to facilitate interdisciplinary collaboration in elementary schools.